Political Monitoring of International Observation Teams on Iraqi Elections After 2003 and Their Popular Evaluation - Shweal, Mohmmed Qassim (Thi Qar Arts Journal, 2024)
International monitoring of legislative elections in newly democratic countries is a fundamental pillar in enhancing confidence in the democratic system, and thus the legitimacy and stability of the political system. This research attempts to shed light on the work of international monitoring teams on elections after the electoral process ends, starting from the announcement of results, and then measuring popular opinion on this monitoring through launching a survey that poses essential questions to clarify the popular stance on international monitoring and evaluate its role in supporting the electoral process and enhancing public confidence in it, which encourages political participation in successive electoral cycles.